Comprehensive analysis of serum tumor markers and BRCA1/2 germline mutations in Chinese ovarian cancer patients - Deng, Hongyu (Mol Genet Genomic Med, 2019)
BACKGROUND: The serum tumor markers has been widely used in ovarian cancer diagnosis. BRCA1/2 germline mutations are the most common predisposing factors for ovarian cancer development. This study aimed to comprehensively investigate serum tumor markers and BRCA1/2 germline mutations and analyze their associations with ovarian cancer. METHODS: Levels of 11 serum tumor markers were examined in ovarian cancer patients and controls with benign gynecologic diseases. By integrating multiplex PCR and next‐generation sequencing technologies, BRCA1/2 germline mutations were analyzed and confirmed by Sanger sequencing. The discriminative models with serum tumor markers and BRCA1/2 mutation status were constructed for ovarian cancer detection and patient stratification. RESULTS: Among 11 markers, six of them were significantly elevated and only beta‐human chorionic gonadotropin (β‐HCG) was significantly reduced in ovarian cancer patients. A total of 54 (23.3%) ovarian cancer patients were found to harbor BRCA1/2 deleterious mutations, and BRCA1/2 mutations were significantly associated with Hereditary Breast and Ovarian Cancer‐related tumors and family history of cancer. Carbohydrate antigen 125 showed a good performance in ovarian cancer detection as a single marker (AUC = 0.799), while a panel of eight markers showed a good performance in BRCA1 mutation detection with an AUC value of 0.974. In addition, a panel of five serum tumor markers combined with BRCA1/2 mutation status showed a good performance in lymph node metastasis prediction (AUC = 0.843). CONCLUSIONS: We found the association between BRCA1/2 germline mutation status and serum tumor marker levels, and identified discriminative models that combined serum tumor markers with BRCA1/2 mutation status for ovarian cancer detection and patient stratification.